CaCo-2 Cells Treated with Clostridium perfringensEnterotoxin Form Multiple Large Complex Species, One of Which Contains the Tight Junction Protein Occludin - Usha Singh; Christina M. Van Itallie; Laura L. Mitic; James M. Anderson; Bruce A. McClane (2000)
The previous model for the action ofClostridium perfringens enterotoxin (CPE) proposed that (i) CPE binds to host cell receptor(s), forming a small (∼90 kDa) complex, (ii) the small complex interacts with other eucaryotic protein(s), forming a large (∼160 kDa) complex, and (iii) the large complex triggers massive permeability changes, thereby inducing enterocyte death. In the current study, Western immunoblot analysis demonstrated that CPE bound to CaCo-2 human intestinal cells at 37 °C forms multiple large complex species, with apparent sizes of ∼200, ∼155, and ∼135 kDa. These immunoblot experiments also revealed that occludin, an ∼65-kDa tight junction protein, is present in the ∼200-kDa large complex but absent from the other large complex species. Immunoprecipitation studies confirmed that occludin physically associates with CPE in large complex material and also indicated that occludin is absent from small complex. These results strongly suggest that occludin becomes associated with CPE during formation of the ∼200-kDa large complex. A postbinding association between CPE and occludin is consistent with the failure of rat fibroblast transfectants expressing occludin to bind CPE in the current study. Those occludin transfectants were also insensitive to CPE, strongly suggesting that occludin expression is not sufficient to confer CPE sensitivity. However, the occludin-containing, ∼200-kDa large complex may contribute to CPE-induced cytotoxicity, because nontoxic CPE point mutants did not form any large complex species. By showing that large complex material is comprised of several species (one containing occludin), the current studies indicate that CPE action is more complicated than previously appreciated and also provide additional evidence for CPE interactions with tight junction proteins, which could be important for CPE-induced pathophysiology.